Translating theory into practice: using action research to introduce a coordinated approach to emotional care - Williams, Anne; Dawson, Susan; Kristjanson, Linda (Elsevier, 2008)
Objective: This paper describes a translational project that explored the feasibility and effect of introducing a coordinated approach to emotional care.Methods: The project was undertaken using Action Research on one ward of St John of God Hospital, Subiaco, Western Australia. A senior Registered Nurse was appointed to provide the leadership and direction to staff regarding emotional care and an education program for staff was provided. The project was evaluated using both quantitative and qualitative data.Results: Data demonstrated an increase in the patient's evaluation of emotional care, although levels were found to fluctuate throughout the project. Factors such as the emotional distress of the staff were hypothesised as impacting on the delivery of emotional care. Conclusion: The approach used in this project was found to be a useful method of improving emotional care. However, the data collected in this study revealed the complexity of emotional care delivery and the possible impact of a number of factors within the environment.Practice implications: Emotional care delivery can be improved by using a coordinated research-based educational approach led by a clinical champion. However, the impact of other factors within the hospital environment needs to be considered and more research is required.